Red blood cell distribution width to albumin ratio as a predictor of mortality in ICU patients with community acquired bacteremia - Xiaoxi Shan; Jing Jiang; Wei Li; Lixia Dong (Scientific Reports)
Abstract Bloodstream infections are globally occurring life-threatening diseases that impose significant societal and economic burdens. This study explored the red cell distribution width (RDW) to albumin ratio (RAR), a novel index derived from RDW, to investigate its relationship with prognosis of bacteremia using propensity score matching (PSM). This retrospective observational cohort study included patients with bacteremia admitted to Yantai Yuhuangding Hospital’s intensive care units from June 2019 to December 2022. PSM was performed to adjust for confounding factors. The relationship between RAR and mortality was assessed using receiver operating characteristic curves, multivariate, and Kaplan–Meier analyses. A total of 411 patients were included. The RAR threshold of 5.824% /g/dL was determined by maximizing the Youden index; the study population was divided into two groups based on this cutoff value. After PSM, 125 pairs of score-matched patients were generated. Using logistic regression analysis, patients with RAR ≥ 5.824% /g/dL exhibited significantly higher mortality than did those with RAR ＜ 5.824% /g/dL in the entire cohort (OR = 3.926, 95% confidence interval (CI): 2.408–6.400, p < 0.001) and the PSM subset (OR = 2.460, 95% CI: 1.411–4.289, p = 0.040). RAR results were consistent when treated as continuous or four-categorical variables (based on quartiles). Similar outcomes were found for 28- and 90-day mortality and septic shock. The areas under the curves of RAR were 0.735, significantly higher than those of albumin or RAR alone. RAR emerges as an independent risk factor for mortality and septic shock in critically ill patients with community-acquired bacteremia, whether considered a continuous or categorized variable, irrespective of PSM adjustment.